The Implementation of Cooperative Learning in the Al-Qur'an Hadith Subject at MIS Mathla'ul Anwar, Pasar Baru, Pesawaran, Lampung, Indonesia - Handayani, Nur; Mardiana, Mardiana; Eka Putra, Arizal (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2026)
This study aims to describe the implementation of the Student Teams Achievement Divisions (STAD) type cooperative learning model in learning the Qur'an Hadith in class V B MIS Mathla'ul Anwar Pasar Baru and evaluate its impact on student activities and collaboration. The approach used is qualitative with the type of field research. Data collection is carried out through observation, interviews, and documentation, then the data is analyzed through a process of reduction, presentation, and conclusion drawn. The findings of the study indicate that the STAD model is carried out in five phases, namely the presentation of materials, the formation of heterogeneous groups, learning activities in teams, individual quizzes, and the awarding of awards. The implementation of this model shifts the focus of learning from teachers to students. STAD has been proven to increase students' active participation, strengthen cooperation and responsibility in groups, and foster motivation and enthusiasm for learning. In addition, students become more courageous to express their opinions, be able to discuss effectively, and show a better understanding of the Qur'an Hadith material. These results show that the STAD model can be used as an alternative effective learning strategy at the Madrasah Ibtidaiyah level.